Management of the Pregnant Inflammatory Bowel Disease Patient on Antitumour Necrosis Factor Therapy: State of the Art and Future Directions - Yvette PY Leung; Remo Panaccione; Subrata Ghosh; Cynthia H Seow (Canadian Journal of Gastroenterology and Hepatology)
Antitumour necrosis factor (anti-TNF) therapy has been a major advance in the treatment of inflammatory bowel disease (IBD) by improving rates of mucosal healing, steroid-free remission, and decreasing rates of hospitalization and surgery. Because IBD affects women in their reproductive years, clinicians have and will continue to be asked in the future about the safety profile of these agents and their potential impact on pregnancy, the developing fetus and newborn. Immunoglobulin G transfer from the mother to fetus begins in the second trimester, with an elevation starting at 22 weeks of gestation and the largest amount transferred in the third trimester. Although research investigating the long-term outcomes of children exposed to anti-TNF therapy in utero is limited, there is no known adverse effect on either pregnancy or newborn outcomes including infectious complications with this class of drugs. The World Congress of Gastroenterology consensus statement on biological therapy for IBD considered infliximab and adalimumab to be low risk and compatible with use during conception and during pregnancy in at least the first two trimesters. Based on a clinical algorithm used at the University of Calgary Pregnancy and IBD clinic (Calgary, Alberta), recommendations have been provided on the management of pregnant patients on anti-TNF therapy, particularly with regard to third-trimester dosing, taking into account disease characteristics of individual patients. When educated about the safety of anti-TNF therapy during pregnancy, patients often choose to continue on therapy during the third trimester.